Language Analysis for the Determination of Origin Current Perspectives and New Directions - Patrick, Peter L.; Schmid, Monika S.; Zwaan, Karin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This comprehensive, up-to-date volume reports on current practices and use of Language Analysis for the Determination of Origin (LADO). Readers will find chapters on how it is done, where it is used, how it is used, and learn about recent developments on the use of LADO reports in judicial practice, and current controversies in the field. LADO is a highly controversial topic, and a relatively new branch of forensic linguistics that is used by most European and some non-European governments. When asylum seekers cannot submit documentary proof of their origin, their language can be analysed in order to assess whether their linguistic profile is in accordance with their stated origin. Around 10,000 such language analyses take place annually. This volume is based on the series of meetings of the Language and Asylum Research Group held between 2010 and 2012 and convened by the editors, and offers a state-of-the art perspective from researchers, practitioners, policymakers and stakeholders working on or with LADO.
Language Analysis for the Determination of Origin (LADO): An Introduction; Peter L. Patrick -- Part I: The Data for LADO -- The interview as an interactional event; Anna De Fina -- "We only want to talk...": Lingua interviews for Linguistic Analyses for the Determination of Origin (LADO); Priska Hubbuch -- Part II: LADO Analysis -- Parameters affecting reliability in dialect attribution; Lars Johan Lundberg -- The role of native speakers in LADO: Are we missing a more important question? Helen Fraser -- LADO as forensic speaker profiling; Paul Foulkes, Peter French and Kim Wilson -- Part III: Complicating factors and case studies -- Language and origin: The perspective of multilingualism; Pieter Muysken -- Trouble in LADO-land: How the brain deceives the ear; Dennis R. Preston -- Language attrition as a problem for LADO; Monika S. Schmid -- The case of the Bajunis; Derek Nurse -- Transnational languages, multilinguals and the challenges for LADO; Susan Fitzmaurice -- Part IV: Use and evaluation of LADO reports by the state -- Legal aspects of LADO from a European perspective: Struggling with the burden of proof? Sarah Craig and Karin Zwaan -- Evaluating expertise: The role of language analysis in the asylum procedure; Ralph Severijns -- On forensic science expertise; Esther M. van Ruth and Michel M.A. Smithuis -- Quality assurance in LADO: Issues of validity; Tim McNamara and Doris Schüpbach.
Keywords: Applied linguistics; Education and state; Political planning; Applied Linguistics; Educational Policy and Politics; Public Policy